Dairy price risk management analysis - Engelmann, Josh (Kansas State University, 2011)
The size of our dairy operation increased from 300 milk cows to 1,700 milk cows in 2003. Once the dairy operation increased, the dependency on milk price to support the entire operation also increased. This was due to the fact that the cropping side of the operation became more devoted to growing feed for the livestock as opposed to producing cash crops. Thus, the increase in the number of milk cows led to decreased diversity in our income potentially increasing the financial risk of the operation. The purpose of this thesis is to study different risk management tools and strategies to aid in the formulation of a risk management plan for milk sales in our operation. Risk management strategies using forward contracts, futures, put options, and cash were analyzed at different time periods and various minimum price levels. The strategies were analyzed over the last ten years (2001-2010) of available price data. Twenty-five risk management strategies were analyzed both with and without set minimum milk prices. Minimum price levels ranged from $14/cwt to $17/cwt in $1 increments. The time frame for the transaction ranged from zero to twelve months prior to production in three-month increments. Based on historical data, risk management strategies can be used to decrease the price risk faced by an operation. The risk management strategies did not affect the average price received at statistically significant levels typically considered. Different risk management opportunities are highlighted that need to be analyzed before fully implementing a risk management plan for dairy operations.
Keywords: Dairy; Risk; Futures; Options; Agriculture, General (0473); Management (0454); Marketing (0338)